Hero stone depicting a hero wielding a sword and shield while riding on a horse - Temples of India Project Team (Jio Institute, 2024)
A fragmentary hero stone depicts the hero riding on horseback, wielding a sword and shield, poised for battle against the enemy. Adjacent to him stands a human figure with folded hands, likely another small figure kneels in front of the standing figure, bowing down. The narrative depicted on this hero stones is similar to other hero stones in the complex.